The Insertion of Religious Moderation as an Effort Build Multicultural Awareness among University Students in the Digital Era - Syamsul Kurniawan; Andry Fitriyanto; Samsul Hidayat; Bayu Suratman; Muhammad Miftah; Suhaimi Suhaimi (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
The rapid development of digital technology underscores the need to strengthen religious moderation in Indonesian Islamic higher education institutions. In this context, universities have a strategic role in teaching students to be tolerant, open-minded, and aware of other cultures. This study aims to analyze the model of implementing religious moderation policies at IAIN Pontianak and to examine its contribution to enhancing students’ multicultural awareness. Using a qualitative research design with a descriptive approach, this study collects data through document analysis, participant observation, and in-depth interviews with institutional leaders, lecturers, and students at IAIN Pontianak. The findings show that the religious moderation policy is implemented through several institutional strategies, including strengthening the Center for Religious Moderation, integrating moderation values into the curriculum, and developing human resources through training and academic programs. These initiatives have fostered inclusive, tolerant, and non-violent attitudes among students, particularly in responding to the challenges of the digital era. The study concludes that systematic and institutionalized policy implementation is crucial for instilling religious moderation in Islamic higher education. The implications of this research highlight the importance of policy-driven educational transformation to reinforce multicultural values and social cohesion. However, this study is limited to a single institutional case; further research can conduct comparative studies across various Islamic universities in Indonesia.